2006
DOI: 10.1111/j.1754-4505.2006.tb01506.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Classification System for Dental Treatment under General Anesthesia

Abstract: The provision of comprehensive care for patients with special needs using dental general anesthesia (DGA) has changed over time, and now includes more complex procedures and the participation of many services. As a result, it is necessary to integrate, organize and describe all of the procedures that are carried out in different DGA settings. The aim of this study was to propose a systematic classification for dental treatment procedures be delivered under DGA, and to compare this classification system with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…22 The information about the time of GA in operative setting room is sparse. 21 In the present study we found that healthy children required more general anesthesia time for their oral rehabilitation. The mean was 185 minutes for healthy and 94 minutes for MCDD children, which was a statistically significant difference (P= 0.0001).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…22 The information about the time of GA in operative setting room is sparse. 21 In the present study we found that healthy children required more general anesthesia time for their oral rehabilitation. The mean was 185 minutes for healthy and 94 minutes for MCDD children, which was a statistically significant difference (P= 0.0001).…”
Section: Discussionsupporting
confidence: 53%
“…21 Since then, we have used this classification to describe the entire process of dental care under DGA rather than individual procedures and to organize and summarize data. There are some important points to note in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy‐one studies that included discussion of treatment under GA were found for evaluation. Among these, only 10 studies were included for the final analysis, based on the inclusion and exclusion criteria shown in Table . The majority of the studies reported on the types of dental treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In their study, Roeters and Burgersdijk provided a classification for treatment under GA, based on treatment provided to 221 handicapped patients. As the oral health care for SNP has evolved with more complex and extensive interventions, a new classification system for dental treatment under GA has been developed, based on the duration of treatment, treatment type, and frequency of procedures, as shown in Figure . The treatment modalities included under GA for SNP were preventive, restorative, and surgical procedures.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, administrative matters of the Brazilian Health System related to the hiring of specialists, the type of funding and costs may explain the low participation of specialized dentists. However, it may be that the general dentist is the best suited professional to perform this type of service, as restorative procedures and extractions are the procedures performed most frequently [16,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%